Extração de óleo da polpa de abacate utilizando gás liquefeito de petróleo pressurizado e dióxido de carbono supercrítico como solventes - Abaide, Ederson Rossi (2016)
In this work two differents solvents were used for extraction, carbon dioxide (CO2) in the supercritical state and pressurized liquefied petroleum gas (LPG). The purpose was to extract the oil from the dried avocado pulp comparing these two solvents regarding yield, the time at which the process occurs, adequacy of adjustment of the proposed model to plotted kinetic and the quality of the product obtained by the analysis of their antioxidant activity and gas chromatography analysis coupled with mass spectrometry. Two experimental designs were used, one for each solvent, having as variables the pressure and the temperature with two levels (-1 and +1), and triplicate of the central point (2² + 3 central point), with response the extraction yield of oil. The construction of the kinetic extraction profiles based on the pressure and temperature conditions of experimental design. For the extraction with supercritical CO2 pressure varied in the range of 15 to 25MPa and the temperature ranged from 313 to 353 K, while for extraction with pressurized LPG, pressure and temperature ranged from 0.5 to 2.5 MPa and 293 and 313 K, respectively. It was possible to observe a significant reduction in extraction time using LPG as a solvent, when compared with CO2, and even better extraction yield (57.95%) for LPG and (39.76%) for CO2 in their best extraction conditions experienced. With regard to modeling, it can be seen the appropriateness of the model Sovová the kinetic extraction profiles by means of the adjustment and the kinetic parameters obtained.